Pengaruh Etos Kerja dan Kepuasan Kerja terhadap Produktivitas Kerja Pegawai di Politeknik Penerbangan - Irfan (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
The research aims to: (1) examine and analyze the effect of work ethic on employee work productivity; (2) testing and analyzing the effect of job satisfaction on employee productivity; and (3) examining and analyzing the effect of work ethic and job satisfaction on employee work productivity. This research is an explanatory study which was conducted in July-October 2020. The research population consisted of 91 employees at the Makassar Aviation Polytechnic. Samples were taken by purposive sampling technique. Data were collected using a questionnaire. The dependent variable of this research is employee work productivity, while the independent variable of this research is work ethic and employee job satisfaction. Data analysis was performed using multiple linear regression method. The results showed that: (1) there is an influence of work ethic on employee work productivity; (2) there is an effect of job satisfaction on employee work productivity; and (3) work ethic and job satisfaction can be predictors of employee productivity. This type of research is research qualitative exploratory. According to Sukmadinata (2015: 60) defines qualitative research as "a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups". The dependent variable in this study is employee work productivity.